1990
DOI: 10.1073/pnas.87.20.8120
|View full text |Cite
|
Sign up to set email alerts
|

Opal phytoliths found on the teeth of the extinct ape Gigantopithecus blacki: implications for paleodietary studies.

Abstract: Identification of opal phytoliths bonded to the enamel surface of the teeth of Gigantopithecus blacki indicates that this extinct ape had a varied diet of grasses and fruits. By using the scanning electron microscope at magnifications of 2000-6000x specific opal phytoliths were observed and photographed on the fossilized teeth of an extinct species. Since opal phytoliths represent the inorganic remains of once-living plant cells, their documentation on the teeth of Gigantopithecus introduces a promising techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
7

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 12 publications
1
55
0
7
Order By: Relevance
“…In addition, microfossil studies on lithic instruments (Piperno and Holst, 1998;Piperno et al, 2000;Barton et al, 1998) reported much lower concentrations of starch than we found in the human teeth. Besides that, the number of phytoliths found in both our teeth samples was lower than that observed in samples from individuals of the late Roman period (Fox et al, 1996), in teeth of an extinct ape (Ciochon et al, 1990) and in herbivore teeth (Middleton and Rovner, 1994). The concentrations of phytoliths in our samples were also very small when compared to that of the starch grains of these same teeth.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In addition, microfossil studies on lithic instruments (Piperno and Holst, 1998;Piperno et al, 2000;Barton et al, 1998) reported much lower concentrations of starch than we found in the human teeth. Besides that, the number of phytoliths found in both our teeth samples was lower than that observed in samples from individuals of the late Roman period (Fox et al, 1996), in teeth of an extinct ape (Ciochon et al, 1990) and in herbivore teeth (Middleton and Rovner, 1994). The concentrations of phytoliths in our samples were also very small when compared to that of the starch grains of these same teeth.…”
Section: Discussionmentioning
confidence: 68%
“…A concentration of 3% HCl in Gigantopitecus blacki teeth did not prevent microwear analyses, in the contrary, the acid was used to clean the teeth prior to this kind of analysis (Ciochon et al, 1990). However, a specific study showed that after 30 min exposure of a neolithic human tooth to a solution of 2.5% hydrochloric acid, no alteration was noticed but, after 2 h exposure the enamel was affected and ''almost all the microwear features were removed'' (King et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of opal phytoliths bonded to the enamel surface of G. blacki indicates this giant ape had a varied diet of grasses and fruits [29]. Compared with the dental microwear of living anthropoids, G. blacki was intermediate between folivorous forms and hard-object specialists, and was most similar to the predominantly frugivorous Pan troglodytes species [30].…”
Section: Diet and Habitatmentioning
confidence: 99%
“…Indopithecus (= Gigantopithecus) is thought to have survived until 7.8 and ~7.3 Ma in Pakistan and India, respectively. Opal phytoliths in molar enamel of Gigantopithecus teeth from China probably indicates a varied diet of grasses (possibly bamboo) and fruits (Ciochon et al, 1990). The new Indopithecus tooth with a large caries indicates that a habitat drier than that preferred by Sivapithecus existed at the Late Miocene in India.…”
Section: Disappearance Of the Siwalik Apesmentioning
confidence: 99%